The Dream Is Over The Crisis of Clark Kerr's California Idea of Higher Education - Marginson, Simon (University of California Press, 2016)
The Dream Is Over tells the extraordinary story of the 1960 Master Plan for Higher Education in California, created by visionary University of California President Clark Kerr and his contemporaries. The Master Plan's equality of opportunity policy brought college within reach of millions of American families for the first time and fashioned the world's leading system of public research universities. The California idea became the leading model for higher education across the world and has had great influence in the rapid growth of universities in China and East Asia. Yet, remarkably, the political conditions supporting the California idea in California itself have evaporated. Universal access is faltering, public tuition is rising, the great research universities face new challenges, and educational participation in California, once the national leader, lags far behind. Can the social values embodied in Kerr's vision be renewed? "The Dream Is Over is an outstanding contribution to the literature on higher education. It should be read not only by a large American audience of scholars, teachers, students, and policy makers, but also by a wider international audience interested in higher education, its successes, its shortcomings, and the policies that have driven both." -JUDITH C. BROWN, Dean of the College of Arts and Humanities, Minerva, and former Vice President for Academic Affairs and Provost at Wesleyan "The Dream is Over is a tour de force by Simon Marginson, whose scholarship is essential for understanding the role of higher education in society today. Through an archeology of the "Californian idea," Marginson analyzes the intellectual and political work that established the Master Plan and the University of California as the city of intellect. He shows how the California model influenced the design of higher education around the world and identifies the forces that have brought it to the brink of ruin. Marginson convincingly argues that higher education in the United States now contributes to the reproduction of social inequality but also provides practical suggestions for how to re-charter the pact between higher education and society." -DR. BRENDAN CANTWELL, Michigan State University and Coordinating Editor of Higher Education SIMON MARGINSON is Professor of International Higher Education at the Institute of Education, University College London, and Director of the ESRC/HEFCE Centre for Global Higher Education. He is also joint editor of the journal Higher Education.